RISKS DURING THE TRANSPORTATION OF DANGEROUS GOODS (Perner's Contacts, 2017)
Paper informs about the transportation of dangerous goods in the EU. It describes the risks that occur during the transportation of dangerous goods and also includes the scenarios of dealing with the emergencies, that creates in the transport. It informs about the legal environment that ensures safety, transport of the dangerous goods by roads, rails and inland waterways. It defines the requirements for the transport of dangerous goods, the ability of each subject of transport chain and the classification and labelling the cargoes.
Keywords: dangerous goods; risk; emergency; crisis management